2018
DOI: 10.1016/j.ejro.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inter- and intra-observer variability of breast density assessments using the fourth and fifth editions of Breast Imaging Reporting and Data System

Abstract: BackgroundBreast density is a well-known independent risk factor for breast cancer and can significantly affect the sensitivity of screening mammograms.ObjectiveWe aimed to evaluate the intra- and inter-observer consistencies of breast density assessments using methods outlined in the fourth and fifth editions of the American College of Radiology (ACR) Breast Imaging Reporting and Data System (BI-RADS) guidelines to determine which method is more reliable.Materials and methodsThree radiologists with subspecial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
(41 reference statements)
2
12
1
Order By: Relevance
“…In the literature, intra-reader agreement levels were found to be substantial and nearly perfect (18,22,23,31,32). Similar to the results reported in the literature, we found a high intra-reader agreement level, suggesting that visual methods might be reproducible without any effect from the experience level of the reader.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the literature, intra-reader agreement levels were found to be substantial and nearly perfect (18,22,23,31,32). Similar to the results reported in the literature, we found a high intra-reader agreement level, suggesting that visual methods might be reproducible without any effect from the experience level of the reader.…”
Section: Discussionsupporting
confidence: 89%
“…A study by Alikhassi et al. ( 32 ), which used a methodology similar to the present study, showed that the percentage of dense breasts was higher when radiologists used the 5th edition of the ACR BI-RADS guidelines than when they used the 4th edition. This finding was not in agreement with those reported in the literature; however, this difference was not found to be statistically significant in their study.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Our findings demonstrate a stable pattern in clinical breast density assessment in the BCSC despite the changes to density assessment guidance in the BI-RADS 5th edition. These findings stand in contrast to prior reader studies (19)(20)(21) and a single institution study (22) that suggested a small increase in dense categories with the BI-RADS 5th edition. The two prior US studies were limited to fellowship-trained breast imagers at a single institution (19,22).…”
contrasting
confidence: 99%